Hybrid Synchronous Motor with Improved Starting Torque - Suvorkova Е. Е. Elena Evgenyevna; Istvan Vajda A. I.; Dementiev Yu. N. Yuriy Nikolaevich; Burulko L. K. Lev Kirillovich (2012, 2012)
Title screen